2017
DOI: 10.3390/ijms19010069
|View full text |Cite
|
Sign up to set email alerts
|

The Glutamatergic System in Primary Somatosensory Neurons and Its Involvement in Sensory Input-Dependent Plasticity

Abstract: Glutamate is the most common neurotransmitter in both the central and the peripheral nervous system. Glutamate is present in all types of neurons in sensory ganglia, and is released not only from their peripheral and central axon terminals but also from their cell bodies. Consistently, these neurons express ionotropic and metabotropic receptors, as well as other molecules involved in the synthesis, transport and release of the neurotransmitter. Primary sensory neurons are the first neurons in the sensory chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 169 publications
(281 reference statements)
2
27
0
Order By: Relevance
“…These observations suggest that the TRP channel increase could be related to the higher infiltration by nervous fibers in pathological samples. These results are aligned with previous studies that identified these channels on axons in peripheral tissues [8]. TRP channels act as sensors of various stimuli in peripheral sensory neurons.…”
Section: Discussionsupporting
confidence: 92%
“…These observations suggest that the TRP channel increase could be related to the higher infiltration by nervous fibers in pathological samples. These results are aligned with previous studies that identified these channels on axons in peripheral tissues [8]. TRP channels act as sensors of various stimuli in peripheral sensory neurons.…”
Section: Discussionsupporting
confidence: 92%
“…SGCs are in close contact with neurons, ensheathing them and playing a role in neurotransmission and glutamate homeostasis [25,259,260,272]. To that end, SGCs express several glutamate transporters, metabotropic glutamate receptors, NMDAR, KR and AMPAR [259,260]. Regarding AMPAR, SGCs express mainly GluA4 and in lesser quantities GluA2/3 but no GluA1 [259,273].…”
Section: Ampar In Other Glial Cellsmentioning
confidence: 99%
“…L-Glutamate is the major excitatory neurotransmitter in the central nervous system. The actions of glutamate are modulated by ionotropic receptors and metabotropic glutamate receptors (mGluRs) (5). Based on sequence homology and signal transduction mechanisms, mGluRs have been divided into groups I, II and III; mGluR4, mGluR6, mGluR7 and mGluR8 are group III mGluRs (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…The actions of glutamate are modulated by ionotropic receptors and metabotropic glutamate receptors (mGluRs) (5). Based on sequence homology and signal transduction mechanisms, mGluRs have been divided into groups I, II and III; mGluR4, mGluR6, mGluR7 and mGluR8 are group III mGluRs (5,6). These receptors can modulate the effect and release of glutamate in the central nervous system (7).…”
Section: Introductionmentioning
confidence: 99%